Prinsip Ekologis Untuk Kehidupan Berkelanjutan Perspektif Teologi Islam: Kajian Atas Kitab Rasail al-Nur Sa`id Nursi - Mudin, Moh Isom; Zarkasyi, Hamid Fahmy; Riyadi, Abdul Kadir (FIKRAH, 2021)
Sa`id Nursi argues that nature and the environment have fixed principles that function to maintain the continuity of life while problems arise when the patterns of human environmental activity tend to contradict these principles so that life is threatened. This paper discusses the principles of ecology according to Sa`id Nursi as the basis for implementing the sustainable living agenda. Primary data of this qualitative study were obtained from Rasail al-Nurwhich was described as well as analyzed using a compare and contrast model with relevant environmental theories. The two findings of this study are that Nursi first built an ecological principle based on the tajalli principle of al-asma al-husna, namely cleansing (at-tandzif) the manifestation of al-Quddus, interdependence (at-tasanud) of al-Fard's manifestation, harmony (at-ta`awun) al-Fard, dynamic balance (at-iqtishad wa al muwawazanah) manifestation of al-hakim. Second, Nursi considers humans to be caliphs because they have the most perfect ecological elements in manifesting the attributes of Allah Almighty. Sa`id Nursi emphasized that the human community must maintain and implement this principle for the sustainability of the nature it occupies. The sustainability of life is directly proportional to the implementation of ecological principles.